Biomechanical factors in the open gingival embrasure region during the intrusion of mandibular incisors: A new model through finite element analysis - Zhang, Yubohan; Gao, Jie; Wang, Xu; Wang, Jihong; Zhang, Xu; Fang, Shishu; Wang, Wei; Ma, Yanning; Jin, Zuolin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Open gingival embrasure (OGE) is a common complication in adults following clear aligner therapy and the influence of gingival or alveolar bone biotype on OGE is of great concern. Unfortunately, due to the limited number of patients with clearaligner therapy and the clinical methods to distinguish the gingival biotype of patients being invasive, it is difficult to carry out clinical studies on the gingival or alveolar bone biotype of the OGE. In the meanwhile, the detailed biomechanics of the occurrence of OGE remains unknown. The goal of this study was to establish a new model to simulate the virtual space region, namely, the OGE region, to investigate the relationship between alveolar bone biotype and the occurrence of OGE, and explore potential biomechanical factors related to OGE. Methods: The OGE region in the interproximal space was established using a filler with a very low modulus of elasticity (1 × 10−6 MPa). To illustrate the biomechanics of OGE more exhaustively, a line was created at the top of the alveolar crest along the proximal tooth root. FEA was then used to analyze the biomechanics of the surrounding tissues, the OGE region and the line at the top of the alveolar crest along the proximal tooth root of the central incisor under two different labial bone thicknesses (thick and thin) with an axial inclination of 80°, 90° and 100°. Results: During intrusion of the incisors in clear aligner therapy, as inclination increased or bone tissue became thinner, the stress in the surrounding tissues [tooth root, alveolar crest, and periodontal ligament (PDL)] was greater. In the OGE region and interproximal alveolar crest, the strain increased with increasing inclination and labial bone thinning. The results from the line at the top of the alveolar crest along the proximal tooth root showed more detailed biomechanics: In all groups, stress and strain were focused on the mesial-labial alveolar crest. Interestingly, our results also demonstrated that when OGE occurs, other complications may arise, including root resorption and bone dehiscence.